Description of a neural sheath tumor of the trigeminal nerve: immunohistochemical and electron microscopy study - Khademi, Bijan (2006)
CONTEXT: Malignant neural sheath tumors of the trigeminal nerve affecting the nasal cavity and the paranasal sinuses are extremely rare. With conventional optical microscopy, their identification is difficult, and it is necessary to confirm them by means of electron microscopy and immunohistochemical techniques. CASE REPORT: The patient was a 41 year old woman with a ten month progressive history of pain followed by painful edema in the left facial region, and with symptoms of bleeding, secre- tion and nasal obstruction. Studies with imaging methods suggested the presence of an expansive process in the left nasal and paranasal cavities. In the biopsy, the histopathological findings from optical microscopy were suggestive of a tumor of neural origin in the trigeminal nerve. Immunohis- tochemical and electron microscopy studies con- firmed that it was a malignant tumor of the neural sheath of the trigeminal nerve. We describe the clinical, radiological, and histological features of this tumor and review the literature.